Autocad 2014 for dummies - Fane, Bill; Byrnes, David 1947- (For dummies)
Put away that pencil and paper and start putting the power of AutoCAD 2014 to work in your CAD projects and designs. From setting up your drawing environment to using text, dimensions, hatching, and more, this guide walks you through AutoCAD basics and provides you with a solid understanding of the latest CAD tools and techniques. You'll also benefit from the full-color illustrations that mirror exactly what you'll see on your AutoCAD 2014 screen and highlight the importance of AutoCAD's Model view, which shows different line weights for printing in different colors.